2021
DOI: 10.1111/codi.15585
|View full text |Cite
|
Sign up to set email alerts
|

Does neoadjuvant FOLFOX chemotherapy improve the prognosis of high‐risk Stage II and III colon cancers? Three years' follow‐up results of the PRODIGE 22 phase II randomized multicentre trial

Abstract: Aim: Neoadjuvant chemotherapy has proven valuable in locally advanced resectable colon cancer (CC) but its effect on oncological outcomes is uncertain. The aim of the present paper was to report 3-year oncological outcomes, representing the secondary endpoints of the PRODIGE 22 trial. Method: PRODIGE 22 was a randomized multicentre phase II trial in high-risk T3, T4 and/ or N2 CC patients on CT scan. Patients were randomized between 6 months of adjuvant FOLFOX (upfront surgery) or perioperative FOLFOX (four cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
2
27
0
4
Order By: Relevance
“…A recent randomized trial reported no additional benefit for perioperative chemotherapy in patients who were clinically diagnosed as high-risk, such as T3, T4, and/or N2 colon cancer on preoperative CT scan. Nevertheless, identifying a subgroup of patients who could benefit from this strategy is warranted 22 . In this respect, preoperative imaging biomarkers that can stratify high-risk groups are essential, and the clinical usefulness of visceral fat-derived classification needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized trial reported no additional benefit for perioperative chemotherapy in patients who were clinically diagnosed as high-risk, such as T3, T4, and/or N2 colon cancer on preoperative CT scan. Nevertheless, identifying a subgroup of patients who could benefit from this strategy is warranted 22 . In this respect, preoperative imaging biomarkers that can stratify high-risk groups are essential, and the clinical usefulness of visceral fat-derived classification needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Однако проведение неоадъювантной химиотерапии не привело к увеличению ни ОВ (3-летний показатель составил 90,4 % в обеих группах, отношение рисков (ОР) 0,85), ни ВБП (76,8 % против 69,2 %, ОР 0,94). Отмечено, что наличие микросателлитной нестабильности (microsatellite instability, MSI) в опухолях было связано с неэффективностью предоперационной химиотерапии (р = 0,05), а поражение 4 и более лимфатических узлов, наоборот, определяло увеличение ОВ при реализации неоадъювантного подхода (р = 0,04) [32].…”
Section: исследования по неоадъювантной химиотерапии при раке ободочн...unclassified
“…[ 1 ] Comprehensive treatment of CC has a better prognosis in its early stage; however, there has been no obvious improvement in advanced CC prognosis for patients who do not respond to adjuvant treatment or radical surgery. [ 1–4 ] After curative‐intent surgery or adjuvant chemotherapy, the recurrence rate is still 27% for stage III CC. [ 5 ] Recurrence occurs in 80% of cases during the first 3 years after resection, and patients after radical resection have a poor prognosis even when radical resection is performed again.…”
Section: Introductionmentioning
confidence: 99%